THE DIFFERENCE OF ACHIEVEMENT BETWEEN THE STUDENTS TAUGHT BY CONTEXTUAL TEACHING AND LEARNING AND DIRECT INSTRUCTION IN MATHEMATICS GRADE VIII OF SMPN 1 TANJUNG MORAWA - Retni Triandini; Pargaulan Siagian (Study Program of Mathematics Education of Unimed Postgraduate Program, 2016)
The type of this study is a quasy-experiment study. The objective of this research is to know: “The students’ mathematics achievement by using contextual teaching and learning (CTL) is higher than by using direct instruction”. The population of this research is all of students in SMPN 1 Tanjung Morawa with total of 972 students. The sampling technique applied was cluster random sampling. The control class that is chosen VIII-5 consisted of 36 students, meanwhile the experiment class that is chosen VIII-2 consisted of 36 students. The instruments are used to measure the students mathematics achievement was a multiple-choice test and the students learning style was questionnaire. The normality test used of Lillie for’s test and the homogeneity test by using Fisher test. The data analysis technique was t-test at the level of significance α = 5%.The study result showed that: “The students mathematic achievement taught by contextual teaching and learning (CTL) is higher than the students mathematics achievement taught by direct instruction, where tcount (1.2349) < ttable (1.9944) and Sig. Contextual (0.015) < 0.05 and Sig. Direct Instruction (0.039) < 0.05”. The level of learning mastery for student or KKM, If student gets a minimum score is greater than or equal 2.66 (KKM ≥ 2.66), so student obtain completeness of learning. The students score is 67.01% (moderate), cumulative learning is 93.06% (very good items questioner). Based on the data analysis result of multiple comparisons by t-test, it can be conclude that the student’s mathematics achievements not have different which is taught by contextual teaching and learning (CTL) with students by direct instruction.